KAJIAN KRITIS TENTANG INOVASI DAERAH TERKAIT PENGEMBANGAN DAN PENGELOLAAN DESA WISATA BERBASIS KOMUNITAS (Jurnal Ilmiah Pariwisata, 2016)
Sutan sjahrir once said: “new if our village do start to move forward over his power own, then all our society, will also up individuals at and progress in all the field, including the field culture”. Look of the advice, should the community welfare is in vilage’s, can be immediately realized, remember village have the potential very large, in various natural resources, resources culture, the characteristics and uniqueness his human, coupled with indorsement village funds almost was 1.5 billion. But ironic if we look at it, why still in rural areas community, still just coming problems hunger, poverty, lost identity and so on, even a lot of which go from village because assume village he live in not were given hope for the future. Problems these problems are real the and trickling in almost all village in indonesian.This, apparently have many provide a to us how to village dioah and managed, because of that village can give hope and welfare for their citizens. The concept of the independence can be realized with a pattern development of backward, with model of development tourist village, here the community called to collectively make a notion how showing potential for many fields including tourism, without damaging and reduce the value of the value local knowledge owned. The outcome of several explained the study a lot of models tourist village, as: tourist village themes culture, tourist village themes potential nature, until tourist village of a religious nature, which some study it reduce on a explaining how village managed in a communal with synchronize with many sides such as; government and private, to shoulder - before build model of development tourist village appropriate to identity the village community. Of all this can be drawn an explanation that it is important comprehend potential in have village, then mengolahna into a activities which is potential to lead on improving the quality of the community, whether materil and moral .Hence we think the development model tourist village relevant to the state of village that were still marginalised.
Keywords: Innovation Regionsi, Tourist Village, Based Regions